2021
DOI: 10.3390/plants10061142
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Phenolic Acids Are Differently Genetically Determined in Leaves, Flowers, and Grain of Common Buckwheat (Fagopyrum esculentum Moench)

Abstract: Common buckwheat (Fagopyrum esculentum Moench) is a valuable source of proteins, B vitamins, manganese, tryptophan, phytochemicals with an antioxidant effect, and the natural flavonoid rutin. Due to its composition, buckwheat supports the human immune system, regulates blood cholesterol, and is suitable for patients with diabetes or celiac disease. The study aimed to compare the allocation of selected phenolic acids (neochlorogenic acid, chlorogenic acid, trans-caffeic acid, trans-p-coumaric acid, trans-sinapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
4
14
2
Order By: Relevance
“…The mean values between years differed and were similar to vitexin, accessions showed higher values of isovitexin in 2020. The obtained results are comparable to the values published by Vollmannova et al [52], who reported 0.010-0.212 mg/g d.w. The content of vitexin in buckwheat grains cultivated in Slovakia, reported the lowest value in the variety 'Ballada' (0.010 mg/g d.w.) but this is not in line with our findings where 'Ballada' had stable and almost six times higher content of vitexin, higher in both experimental years (66.91 ± 1.34 ug/g d.w. for 2019 and 53.50 ug/g d.w. for 2020).…”
Section: Phenolic Compounds Contentsupporting
confidence: 91%
See 4 more Smart Citations
“…The mean values between years differed and were similar to vitexin, accessions showed higher values of isovitexin in 2020. The obtained results are comparable to the values published by Vollmannova et al [52], who reported 0.010-0.212 mg/g d.w. The content of vitexin in buckwheat grains cultivated in Slovakia, reported the lowest value in the variety 'Ballada' (0.010 mg/g d.w.) but this is not in line with our findings where 'Ballada' had stable and almost six times higher content of vitexin, higher in both experimental years (66.91 ± 1.34 ug/g d.w. for 2019 and 53.50 ug/g d.w. for 2020).…”
Section: Phenolic Compounds Contentsupporting
confidence: 91%
“…An unusually high amount of quercetin (66.88 ± 0.58 ug/g d.w.) was detected in ‘Temnica na Krasu’ in 2020. However, this was an exception among all the studied buckwheat samples and the other values observed were more or less at the same level but at a lower level in comparison with data presented by Vollemannová et al [ 52 ]. Quercitrin in the buckwheat collection was found at a level of 3.87 ± 2.66 ug/g d.w. for 2020 and 1.19 ± 0.98 ug/g d.w. for 2019.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations